Oral health-related quality of life of community-dwellers in the canton of Bern, Switzerland - Roberta Borg-Bartolo; Andrea Roccuzzo; Christian Tennert; Maria Prasinou; Maurus Jäggi; Pedro Molinero-Mourelle; Michael M. Bornstein; Guglielmo Campus (Acta Odontologica Scandinavica)
Objective: The study aims to describe and analyze the oral health-related quality of life (OHRQoL) of persons aged ≥45 years in the canton of Bern, Switzerland.